2012
DOI: 10.1007/bf03396944
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Social Role of Contemporary Chinese Universities in the Reform Era

Yuan Xun

Abstract: In the last three decades, along with rapid economic and social changes in China, dramatic changes have taken place in Chinese higher education, where Chinese universities have been experiencing a variety of systematic reforms. Chinese universities are also facing some new issues yet they have largely neglected the task of establishing their own internal values and taking up their social responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is worth noting that the era of the knowledge‐based economy has resulted in innovation becoming mainstream worldwide. With the development of society, universities have increasingly become nonnegligible forces in both scientific and technological innovation (Cai, 2010; Xun, 2012). Correspondingly, many university teachers are also engaged in research innovation.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the era of the knowledge‐based economy has resulted in innovation becoming mainstream worldwide. With the development of society, universities have increasingly become nonnegligible forces in both scientific and technological innovation (Cai, 2010; Xun, 2012). Correspondingly, many university teachers are also engaged in research innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these issues and problems, academic nationalism largely contributes to the implementation of state-led initiatives such as the WCUs campaign, and to some extent, to the cohesion among Chinese academics toward achieving such a common goal. Nonetheless, heated debate on the standard and components of a WCU raised concerns over the loss of a university spirit—an independent ethos cohering the Chinese academic community to pursue the truth and serve the public good (Xun, 2012; Zha & Hayhoe, 2014).…”
Section: Academic Identity In Chinese He Contextmentioning
confidence: 99%
“…There were hot debates over what should constitute a world-class university, and how far Chinese universities are from world standing. The debates eventually revealed that Chinese universities largely lack a university spirit, i.e., an independent ethos that works to hold together an academic community in its pursuit of the truth (Xun, 2012). In the words of a Chinese university president, "the university spirit in China is really lost.…”
Section: Chinese Higher Education Is Facing a Crisismentioning
confidence: 99%